Recent Advances in the Understanding of Molecular Mechanisms of Resistance in Noctuid Pests - Le Goff, Gaelle; Nauen, Ralf (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book brings together the papers published in the Special Issue "Recent advances in the understanding of molecular mechanisms of resistance in Noctuid pests" in the journal Insects in 2021. It contains 10 articles that are either original results or reviews. The focus is on insects of the noctuid family, as they are among the most devastating crop pests on the planet. Understanding the molecular mechanisms that allow these insects to become resistant to insecticides is essential for the implementation of sustainable control methods and resistance management strategies.